In situ XRD analysis of Ni(Pt)/Si(100) reactions in low temperature regime ≤400°C - Mangelinck, D. (2013)
The key feature of this paper is to highlight the use of an in situ XRD technique to the study of the initial reaction of Ni(Pt) on Si(100) isothermally. The concentration of Ni and Pt as a function of time in the low temperature range of less than 400 °C was evaluated. The XRD results show that the solid state reaction started with a outdiffusion of Ni from the Ni(Pt) alloy during the formation of Ni2Si prior to the formation of Ni(Pt)Si. This in situ technique is important for the characterization and the study of the nucleation and kinetics of the first phase formation of advanced alloy silicides.